Triplet Harvesting with a Simple Aromatic Carbonyl. Issue 17 (20th July 2017) - Torres Ziegenbein, Christian; Fröbel, Sascha; Glöß, Maria; Nobuyasu, Roberto S.; Data, Przemyslaw; Monkman, Andrew; Gilch, Peter
Abstract: The efficiency of organic light‐emitting diodes crucially depends on triplet harvesters. These accept energy from triplet correlated electron hole pairs and convert it into light. Here, experimental evidence is given that simple aromatic carbonyls, such as thioxanthone, could serve this purpose. In these compounds, the emissive 1 ππ* excitation may rapidly equilibrate with an upper triplet state ( 3 nπ*). This equilibrium may persist for nanoseconds. Population of the 3 nπ* state via energy transfer from an electron hole pair should result in fluorescence emission and thereby triplet harvesting. To demonstrate the effect, solutions of 1, 4‐dichlorobenzene (triplet sensitizer) and thioxanthone (harvester) were excited at 266 nm with a nanosecond laser. The emission decay reveals a 100 ns decay absent in the thioxanthone only sample. This matches predictions for an energy transfer limited by diffusion and gives clear evidence that thioxanthone can convert triplet excitations into light. Abstract : Aromatic carbonyls such as thioxanthone are shown to be potential triplet harvesters for organic light‐emitting diodes.